Assessment of muscle contractile properties at acute moderate altitude through tensiomyography - Morales-Artacho, A. J.; Padial, P.; Rodriguez-Matoso, D.; Rodriguez-Ruiz, D.; Garcia-Ramos, A.; Garcia-Manso, J. M.; Calderon, C.; Feriche, B. (High Altitude Medicine & Biology, 2015)
Under hypoxia, alterations in muscle contractile properties and faster fatigue development have been reported. This study investigated the efficacy of tensiomyography (TMG) in assessing muscle contractile function at acute moderate altitude. Biceps femoris (BF) and vastus lateralis (VL) muscles of 18 athletes (age 20.1 ± 6.1 years; body mass 65.4 ± 13.9 kg; height 174.6 ± 9.5 cm) were assessed at sea level and moderate altitude using electrically evoked contractions on two consecutive days. Maximum radial displacement (Dm), time of contraction (Tc), reaction time (Td), sustained contraction time (Ts), and relaxation time (Tr) were recorded at 40, 60, 80, and 100 mA. At altitude, VL showed lower Dm values at 40 mA (p = 0.008; ES = -0.237). Biceps femoris showed Dm decrements in all electrical stimulations (p < 0.001, ES > 0.61). In VL, Tc was longer at altitude at 40 (p = 0.031, ES = 0.56), and 100 mA (p = 0.03, ES = 0.51). Regarding Td, VL showed significant increases in all electrical intensities under hypoxia (p = 0.03, ES = 0.33). TMG appears effective at detecting slight changes in the muscle contractile properties at moderate altitude. Further research involving TMG along with other muscle function assessment methods is needed to provide additional insight into peripheral neuromuscular alterations at moderate altitude.